Electrospun eri silk fibroin scaffold coated with hydroxyapatite for bone tissue engineering applications - Andiappan, Muthumanickkam (Prog Biomater, 2013)
Natural biomaterials such as collagen, silk fibroin, and chitosan, and synthetic biopolymers such as polylactic acid, polycaprolactone, polyglycolic acid, and their copolymers are being used as scaffold for tissue engineering applications. In the present work, a fibrous mat was electrospun from eri silk fibroin (ESF). A composite of hydroxyapatite (Hap) and the ESF scaffold was prepared by soaking the ESF scaffold in a solution of calcium chloride and then in sodium diammonium phosphate. The average tensile stress of the pure ESF and hydroxyapatite-coated ESF scaffold (ESF-Hap) was found to be 1.84 and 0.378 MPa, respectively. Pure ESF and ESF-Hap scaffolds were evaluated for their characteristics by a themogravimetric analyzer and Fourier transform infrared spectroscope. The crystallinity and thermal stability of the ESF-Hap scaffold were found to be more than that of uncoated eri silk nanofiber scaffold. The water uptake of the pure ESF and ESF-Hap scaffolds was found to be 69% and 340%, respectively, in distilled water as well as phosphate buffer saline. The hemolysis percentage of both scaffolds was less than 5%, which indicate their good blood compatibility. The cytocompatibility studied by 3-(4,5-dimethyl) thiazol-2-yl-2,5-dimethyl tetrazolium bromide assay showed that the scaffold is biocompatible. To assess cell attachment and growth on the scaffold, human mesenchymal stem cells were cultured on the scaffolds. The results from scanning electron microscopy and fluorescent microscopy showed a notable cellular growth and favorable morphological features. Hence, the ESF-Hap scaffold is better suited for cell growth than the pure ESF scaffold. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2194-0517-2-6) contains supplementary material, which is available to authorized users.